Imaging of retroperitoneal haemorrhage revealing median arcuate ligament syndrome - Younes El Hassani; Meriem Haloua; Badreeddine Alami; Meryem Boubbou; Mustapha Maaroufi; Moulay Youssef Alaoui Lamrani (South African Journal of Radiology, 2021)
Coeliac artery compression stenosis caused by the median arcuate ligament can lead to aneurysm formation in the pancreatico-duodenal arteries that can eventually result in a spontaneous rupture leading to retroperitoneal haemorrhage. In this case series, we describe the cases of three patients, all presenting with sudden epigastric pain, diagnosed as spontaneous haematoma, complicating a median arcuate ligament syndrome.